Dampak Fluktuasi CPO Terhadap Program Percepatan Penyaluran Ekspor CPO Dalam Pemulihan Ekonomi Indonesia - Nurfadjri, Annisa (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
Indonesia as a developing country relies heavily on its natural wealth in the plantation sector which contributes to economic growth. CPO price fluctuations are influenced by soybeans, which are CPO substitute products, these CPO fluctuations greatly affect the amount of production and demand for CPO itself and have an impact on the price of Fresh Fruit Bunches (FFB) and the increase in global CPO prices. This study uses a type of qualitative research method that is a descriptive analysis using library research as a secondary data collection technique. Responding to the issue of CPO, the Indonesian government set a policy to accelerate the distribution of CPO exports by setting export duties and export tariffs in the program to accelerate the distribution of CPO and its derivatives through exports as regulated in PMK/102/PMK.010/22. In addition to this policy, the government also sets service tariffs in the Public Service Agency of the Palm Oil Plantation Fund Management Agency (BPDPKS) aimed at stabilizing FFB prices and optimizing trade and production of CPO and its derivative products PMK 103/PMK.05/2022. The program to accelerate the distribution of CPO exports is carried out by the provisions stipulated by the government in legislation through intensive supervision and research on exporters, which is expected to increase export volumes and stabilize FFB prices and contribute to increasing Indonesia's economic growth through an increase in foreign exchange.